2004
DOI: 10.1554/03-731
|View full text |Cite
|
Sign up to set email alerts
|

Historical Diversification of Migration Patterns in a Passerine Bird

Abstract: Migratory strategies of birds require complex orientation mechanisms, morphological adaptations, and life-history adjustments. From an evolutionary perspective, it is important to know how fast this complex combination of traits can evolve. We analyzed mitochondrial control-region DNA sequences in 241 blackcaps (Sylvia atricapilla) from 12 populations with different migratory behaviors. The sample included sedentary populations in Europe and Atlantic archipelagos and migratory populations with different distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 46 publications
12
120
2
Order By: Relevance
“…This is exactly what we see in figure 2, where there are more young pairs with low differentiation in the divide group (open circles, bottom left hand corner). Sister pairs that form divides today also provide support for this expectation, as many of the migratory divides described to date occur between taxa that exhibit low levels of phenotypic divergence, including subspecies of willow warblers [9], populations of European blackcaps [64] and subspecies groups of the Swainson's thrush. For example, two groups of Swainson's thrushes form a migratory divide in western North America, where they differ in song, morphology, and colour [65,66].…”
Section: Discussionmentioning
confidence: 86%
“…This is exactly what we see in figure 2, where there are more young pairs with low differentiation in the divide group (open circles, bottom left hand corner). Sister pairs that form divides today also provide support for this expectation, as many of the migratory divides described to date occur between taxa that exhibit low levels of phenotypic divergence, including subspecies of willow warblers [9], populations of European blackcaps [64] and subspecies groups of the Swainson's thrush. For example, two groups of Swainson's thrushes form a migratory divide in western North America, where they differ in song, morphology, and colour [65,66].…”
Section: Discussionmentioning
confidence: 86%
“…In most cases, these flyways have been delimited based on mark-recapture data but, in many species, they are also supported by the molecular data (mostly mtDNA), that is, in passerines (Ruegg and Smith, 2002;Clegg et al, 2003;Pérez-Tris et al, 2004), waders (Wennerberg, 2001) and several species of waterfowl (Scribner et al, 2001;Gay et al, 2004). Similarly, Friesen et al, (2007) found that a majority of seabirds with discontinuous distributions on the breeding or wintering grounds showed some genetic substructure.…”
Section: Genetic Differentiation and Migratory Dividesmentioning
confidence: 97%
“…If powered flight is an integral part of a species' lifestyle, and if BMR reflects these demands, then one should not expect differences in BMR between migrant and temperate resident groups. Alternatively, because tropical migrants developed the migratory habit in recent geological history (34)(35)(36)(37)(38), and because they breed in a benign thermal environment, one might predict that their pace of life is more similar to tropical birds. Some authors have suggested that Neotropical migrants have lower fecundity and higher survival than do temperate residents, patterns consistent with a low rate of energy expenditure (35).…”
mentioning
confidence: 99%